2019
DOI: 10.3390/medicina55060288
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Boxing Matches on Metabolic, Hormonal, and Inflammatory Parameters in Male Elite Boxers

Abstract: Background and objectives: Boxing is a popular combat sport that requires high intensity and cooperation. However, there are limited data about the influence of boxing matches on blood parameters. The purpose of the present study was to investigate the match-induced changes in the metabolic, hormonal, and inflammatory status in male elite boxers. Materials and methods: High-level 20 male boxers with more than 5 years experience in boxing voluntarily participated in this study. Venous blood samples of the boxer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 29 publications
1
16
1
6
Order By: Relevance
“…[36][37][38] Addition of hydrocortisone alone at a physiological concentration to DMEM media (supplemented with 10% FCS, 1% P/S) improved the barrier upon airlift cultivation significantly in a concentration-dependent manner. 39,40 As further supplement, we tested retinoic acid (RA) in DMEM without serum as RA is often described to enhance the barrier. 41 However, RA did not show any enhancement in our model (supplementary Figure S2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[36][37][38] Addition of hydrocortisone alone at a physiological concentration to DMEM media (supplemented with 10% FCS, 1% P/S) improved the barrier upon airlift cultivation significantly in a concentration-dependent manner. 39,40 As further supplement, we tested retinoic acid (RA) in DMEM without serum as RA is often described to enhance the barrier. 41 However, RA did not show any enhancement in our model (supplementary Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“… 36 - 38 Addition of hydrocortisone alone at a physiological concentration to DMEM media (supplemented with 10% FCS, 1% P/S) improved the barrier upon airlift cultivation significantly in a concentration-dependent manner. 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…6,19 However, this increase was not significant compared with that in the control group according to some sources [25][26][27] which conclude that exercise does not stimulate urea production. However, some studies 28,29 said that no changes are found in the plasma levels of urea. The present study indicated that urea increase is statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…These changes also contribute to the reduction of overtraining and adaptation failures (Chernozub, 2018;Spada, et al, 2018;Kistner, et al, 2019;Omassoli, et al, 2019). Studying the features of biochemical control in the process of monitoring the functional state during fitness training, a number of researchers (Futornyi, et al, 2016;Stajer, et al, 2018;Kılıc, et al, 2019) stated that the nature of changes in creatinine concentration clearly reflected the course of adaptation-compensatory responses to physical stimuli in conditions of creatine phosphokinase mechanism of energy supply of intense muscular activity. The obtained results, which at the beginning of the survey showed a decrease in creatinine concentration in blood serum of untrained men of both groups, regardless of the peculiarities of the training load regimes, coincide with the data of experimental studies, used for sprint distance running (200 m, 400 m, 800 m) as training loads (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the constant increase in training loads, the body undergoes significant metabolic changes to ensure the necessary level of training. However, long-term functioning of the body in conditions of constant muscular tension without appropriate mechanisms of training load regulation will lead not only to exhaustion of functional body reserves, but also to failure of adaptation (Butova, et al, 2011;Kılıc, et al, 2019;Kistner, et al, 2019). The use of blood biochemical parameters for the diagnosis of athletes' functional state in the course of training activity allows determining the limits of adequacy of training load parameters to the primary level of body adaptation to stress stimuli of the appropriate character at the beginning of studies (Fomin, et al, 2006;Rubio-Arias, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%